Indications for cardiovascular magnetic resonance in children with congenital and acquired heart disease: an expert consensus paper of the Imaging Working Group of the AEPC and the Cardiovascular Magnetic Resonance Section of the EACVI. (5th March 2015) - Valsangiacomo Buechel, E.R.; Grosse-Wortmann, L.; Fratz, S.; Eichhorn, J.; Sarikouch, S.; Greil, G.F.; Beerbaum, P.; Bucciarelli-Ducci, C.; Bonello, B.; Sieverding, L.; Schwitter, J.; Helbing, W.A.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> This article provides expert opinion on the use of cardiovascular magnetic resonance (CMR) in young patients with congenital heart disease (CHD) and in specific clinical situations. As peculiar challenges apply to imaging children, paediatric aspects are repeatedly discussed. The first section of the paper addresses settings and techniques, including the basic sequences used in paediatric CMR, safety, and sedation. In the second section, the indication, application, and clinical relevance of CMR in the most frequent CHD are discussed in detail. In the current era of multimodality imaging, the strengths of CMR are compared with other imaging modalities. At the end of each chapter, a brief summary with expert consensus key points is provided. The recommendations provided are strongly clinically oriented. The paper addresses not only imagers performing CMR, but also clinical cardiologists who want to know which information can be obtained by CMR and how to integrate it in clinical decision-making.